Single‐Cell Analysis: Toward High‐Dimensional Single‐Cell Analysis of Graphene Oxide Biological Impact: Tracking on Immune Cells by Single‐Cell Mass Cytometry (Small 21/2020). Issue 21 (28th May 2020) - Orecchioni, Marco; Bordoni, Valentina; Fuoco, Claudia; Reina, Giacomo; Lin, Hazel; Zoccheddu, Martina; Yilmazer, Acelya; Zavan, Barbara; Cesareni, Gianni; Bedognetti, Davide; Bianco, Alberto; Delogu, Lucia Gemma
Abstract : The cover, inspired by a famous album cover by Pink Floyd, represents the transformation of the "dark" undetected signal side of graphene into a visible signal, thanks to a specific functionalization with ZnS‐doped AgInS2 nanocrystals, allowing its tracking on the complex mix of human peripheral blood mononuclear cells at the single cell level, as presented in article number 2000123, by Davide Bedognetti, Alberto Bianco, Lucia Gemma Delogu, and co‐workers. The authors thank Fabio Del Regno for the cover design. Image credit: Davide Bedognetti, Lucia Gemma Delogu, and Fabio Del Regno.